2018
DOI: 10.1177/0956462418800872
|View full text |Cite
|
Sign up to set email alerts
|

Field performance evaluation of dual rapid HIV and syphilis tests in three antenatal care clinics in Zambia

Abstract: This cross-sectional study of 3212 pregnant women assessed the field performance, acceptability, and feasibility of two dual HIV/syphilis rapid diagnostic tests, the Chembio DPP HIV-syphilis Assay and the SD Bioline HIV/syphilis Duo in antenatal clinics. Sensitivity and specificity for HIV and syphilis were calculated compared to the rapid Determine HIV-1/2 with Uni-Gold to confirm positive results for HIV and the Treponema pallidum particle agglutination assay for syphilis. RPR titers ≥1:4 were used to define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 14 publications
(29 reference statements)
1
30
0
Order By: Relevance
“…52.0% screened when tests supplies available Nkamba et al (2017) [ 57 ] TP Qualitative DRC, Zambia ANC (urban) Pregnant women, clinic administrators, and HCWs DRC: Alere Determine syphilis TP Zambia: SD Bioline Syphilis 3.0 Fingerprick blood Standalone project. POCT results determine treatment Testing and treatment at first ANC visit acceptable to both providers and patients Althabe et al (2019) [ 58 ] TP Cluster RCT DRC, Zambia ANC (urban) Pregnant women DRC: Alere Determine Syphilis TP test Zambia: SD Bioline Syphilis 3.0 Fingerprick blood Integrated into routine care Intervention: 99.9% Control: 93.8% Behavioural components implemented with a compliance rate between 88 and 100% what was planned No stockouts of supplies for screening or treatment Kasaro et al (2019) [ 59 ] TP Field evaluation Zambia ANC (urban) Pregnant women SD BIOLINE HIV/Syphilis Duo Test Chembio Dual Path Platform HIV-Syphilis Assay Fingerprick blood Standalone project. No discussion of treatment 99.7% preferred the dual test over single tests Both dual RDTs received high and similar feasibility scores from staff Tinajeros et al (2017) [ 60 ] TP Mixed methods Bolivia ANC (urban) HCWs Clinical records of pregnant women Garcia et al (2013) [ 61 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…52.0% screened when tests supplies available Nkamba et al (2017) [ 57 ] TP Qualitative DRC, Zambia ANC (urban) Pregnant women, clinic administrators, and HCWs DRC: Alere Determine syphilis TP Zambia: SD Bioline Syphilis 3.0 Fingerprick blood Standalone project. POCT results determine treatment Testing and treatment at first ANC visit acceptable to both providers and patients Althabe et al (2019) [ 58 ] TP Cluster RCT DRC, Zambia ANC (urban) Pregnant women DRC: Alere Determine Syphilis TP test Zambia: SD Bioline Syphilis 3.0 Fingerprick blood Integrated into routine care Intervention: 99.9% Control: 93.8% Behavioural components implemented with a compliance rate between 88 and 100% what was planned No stockouts of supplies for screening or treatment Kasaro et al (2019) [ 59 ] TP Field evaluation Zambia ANC (urban) Pregnant women SD BIOLINE HIV/Syphilis Duo Test Chembio Dual Path Platform HIV-Syphilis Assay Fingerprick blood Standalone project. No discussion of treatment 99.7% preferred the dual test over single tests Both dual RDTs received high and similar feasibility scores from staff Tinajeros et al (2017) [ 60 ] TP Mixed methods Bolivia ANC (urban) HCWs Clinical records of pregnant women Garcia et al (2013) [ 61 ] ...…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 14 , 15 As a result, these infections are still reported to cause adverse birth outcomes. 16 , 17 Recent studies in SSA have shown a high prevalence of curable STIs amongst pregnant women, and therefore the burden of STIs and HIV in SSA remains a significant threat to reproductive health. 18 , 19 , 20 Women infected with STIs can experience a variety of symptoms, including vaginal itching or irritation, vaginal discharge and dysuria, as well as more severe complications such as pelvic inflammatory disease and fallopian tube pathology.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, other rapid tests have been developed that offer combined treponemal antibody and HIV antibody testing. 22,23 Although these types of rapid tests are not yet available in Malawi due to cost, the integration of both types of rapid test into one promises more accurate syphilis (and HIV) diagnosis in resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%